2017
DOI: 10.1002/brb3.872
|View full text |Cite
|
Sign up to set email alerts
|

Cortical morphology in patients with transient global amnesia

Abstract: ObjectiveThis study evaluated alterations in cortical morphology in patients with transient global amnesia (TGA).Materials and MethodsDiagnoses of TGA occurred at our hospital. Evaluation involved a structured interview to obtain clinical information and a brain magnetic resonance imaging scan. We analyzed whole‐brain T1‐weighted MRI data using FreeSurfer 5.1. Measures of cortical morphology, such as thickness, surface area, volume, and curvature were compared between patients with TGA and healthy controls. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Only studies using diffusion-weighted magnetic resonance imaging (MRI) have consistently shown that the acute stage of TGA is associated with precise focal lesions in the hippocampus [4,5]. In addition, we recently used quantitative analysis of MRI to demonstrate that patients with TGA have significant gray matter volume reductions in several regions, such as hippocampus, cingulum, and cerebellum [6]. Patients with TGA also have significant alterations in cortical thickness in several regions of frontal, temporal, parietal, and occipital lobes of bilateral hemisphere [7].…”
Section: Introductionmentioning
confidence: 99%
“…Only studies using diffusion-weighted magnetic resonance imaging (MRI) have consistently shown that the acute stage of TGA is associated with precise focal lesions in the hippocampus [4,5]. In addition, we recently used quantitative analysis of MRI to demonstrate that patients with TGA have significant gray matter volume reductions in several regions, such as hippocampus, cingulum, and cerebellum [6]. Patients with TGA also have significant alterations in cortical thickness in several regions of frontal, temporal, parietal, and occipital lobes of bilateral hemisphere [7].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the VBM results, greater hippocampal GMV in TGA+ vs TGA- was unexpected and appears at odds with past research demonstrating that patients with TGA have significant GMV reduction in the hippocampus ( Park et al, 2015 ) and widespread alterations in cortical morphology (including cortical thickness and volume) compared to healthy controls ( Kim et al, 2017 ). In our study, differences in GMV were mainly located within the CA1 subfield of the hippocampus.…”
Section: Discussionmentioning
confidence: 56%
“…26 To compare the cortical thickness between patients and controls we performed an ROI analysis, which is potentially more sensitive than the voxel-based approach previously used in patients with TGA. 8 Decreased cortical thickness involved the orbitofrontal, cingulate, and inferior temporal cortices of patients with TGA. Interestingly, several regions of the limbic network showed alterations of both structural connectivity and cortical thickness (left subcallosal gyrus, left lateral orbital sulcus, left middle anterior cingulate cortex, and right opercular inferior frontal gyrus), further strengthening our results.…”
Section: Characteristics Of Patientsmentioning
confidence: 99%
“…Using cortical morphometry, pre-existing structural abnormalities were reported in patients with TGA mainly involving the default mode network. 7,8 The thalamus and the prefrontal cortex have been reported to be functionally altered during TGA by using positron emission tomography assessment. [9][10][11] Using single-photon emission CT, Jang et al 12 found that anterior lesions on DWI were associated with hypoperfusion of the frontal and anterior temporal areas whereas posterior lesions were associated with hypoperfusion of the parietal, posterior temporal, occipital, and cerebellar areas.…”
mentioning
confidence: 99%